Seroprevalence of human brucellosis among the tribal and non-tribal population residing in an eastern state of India: Findings from the state-wide serosurvey - Parai, Debaprasad; Sahoo, Subrat Kumar; Pattnaik, Matrujyoti; Swain, Aparajita; Peter, Annalisha; Samanta, Lopamudra Jena; Pradhan, Rashmita; Choudhary, Hari Ram; Nahak, Kanhu Charan; Pati, Sanghamitra; Bhattacharya, Debdutta (Frontiers in Microbiology, 2022)
Background Brucellosis is a neglected zoonotic disease found predominantly in lower- and middle-income countries (LMICs), causing significant public health concern in India. The objective of this study was to assess the prevalence of human brucellosis in Odisha, India among community members involved in animal husbandry as a common practice. Method This cross-sectional study included 817 adult participants from 11 districts in Odisha. Four districts from the Northern division, four districts from the Central division, and three districts from the Southern division were selected for the study. Blood samples were collected during a COVID-19 serosurvey in Odisha conducted from 1st to 17th September 2021. Immunoglobulin-G (IgG) antibodies were measured against Brucella using a commercial ELISA kit. Point estimates at 95% confidence intervals (CIs) and adjusted odds ratio were calculated. Results The overall prevalence of anti-Brucella IgG antibodies was calculated at 16.65% (95% CI: 14.19–19.42). The highest seropositivity was found in Sambalpur district (29.73%; 95% CI: 16.43–47.16) and the lowest was determined in Mayurbhanj district (4.44%; 95% CI: 0.99–15.60). Compared to males, females were more prone to contracting the disease (AOR: 1.13; 95% CI: 1.05–1.67). Participants from rural settings had higher prevalence of anti-Brucella IgG antibodies than urban dwellers (AOR: 4.53; 95% CI: 1.73–11.86). Conclusion This study revealed that human brucellosis was associated with sociodemographic factors like gender, living settings, and household numbers. To prevent brucellosis, screening should be initiated, infected humans should be treated early, and the public should be educated about risk factors and preventive measures.